KAJIAN PERATURAN GUBERNUR JAWA BARAT TENTANG PENGGUNAAN BATIK TRADISIONAL DAN UPAYA PENCAPAIAN INDIKASI GEOGRAFIS - Saftiyaningsih Ken Atik; Mochamad Djalu Djatmiko (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2020)
The potential strength of traditional West Java batik crafts has grown and developed in 27 regencies/cities spread from the eastern part of the Cirebon district to the western end of West Java, Depok Municipality. The diversity of styles and variations of traditional batik in West Java is a source of strength that is not shared by other provinces. This research uses an empirical juridical approach method or a legislative approach to recognize the regulations that are already running in the community as well as descriptive-analytical research specifications using primary data and secondary data. The superiority of West Java batik has been proven to color the treasury of Indonesian batik along with other traditional batiks. Government support, in this case, the Governor of West Java Province through regulations and Governor's Decree is expected to increase the productivity and glory of traditional West Java batik related to economic potential and as a form of support for the West Java Regional Government in the Regional Cultural Advancement program that has been stipulated in Law No . 5 of 2007. This research is expected to give birth to the decision of the Governor of West Java regarding the use of traditional batik products (original batik) and a variety of typical decoration of West Java batik. West Java society in general.